Job Satisfaction Among Millennial Civil Servants In Tasikmalaya City: The Mediating Role Of Work Motivation In The Influence Of Compensation, Workload, And Spiritual Intelligence - Sialana, Ruswan Fladimer; Mulyana, Deden; Komaludin, Ade (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2025)
This study investigates the influence of compensation, workload, and spiritual intelligence on job satisfaction among millennial civil servants in the Tasikmalaya City Government, with work motivation as a mediating variable. Using Partial Least Square – Structural Equation Modeling (PLS-SEM), the findings reveal that compensation, workload, and spiritual intelligence significantly and positively affect both work motivation and job satisfaction. Furthermore, work motivation significantly and positively impacts job satisfaction. Crucially, work motivation is confirmed to mediate the relationship between compensation, workload, spiritual intelligence, and job satisfaction. These results underscore the importance of understanding factors influencing millennial civil servants' motivation to enhance human resource management and foster a more productive, innovative, and loyal workforce within government institutions..